Kelayakan Finansial Usahatani Kentang di PT. Fujitake Shouten, Nagasaki, Jepang - Ila Amanah Lillah (Journal of Agribusiness, Social and Economic, 2026)
This study aimed to evaluate the financial feasibility of potato farming at PT Fujitake Shouten Co., Ltd., Nagasaki Prefecture, Japan. A quantitative descriptive approach with a case study design was employed. Primary data were collected through direct observation, structured interviews, and documentation during an internship conducted from November 2023 to July 2024. Financial feasibility was assessed using production cost analysis (TC = FC + VC), total revenue (TR = Q × P), net income, Revenue-Cost (R/C) Ratio, Net Present Value (NPV), Internal Rate of Return (IRR), and Net Benefit-Cost (Net B/C) Ratio. The investment was evaluated over a five-year period using a discount rate of 5%. The results revealed that the total production cost was IDR 1,250,000,000, while total revenue reached IDR 1,716,000,000, resulting in a net income of IDR 466,000,000. The financial indicators showed an R/C Ratio of 1.37, a positive NPV of IDR 767,780,000, an IRR of 37.5%, and a Net B/C Ratio of 1.61. These findings demonstrate that potato farming at PT Fujitake Shouten Co., Ltd. is financially feasible and economically profitable, indicating strong potential for sustainable long-term development.